The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00394-017-1443-x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and physical activity and the risk of diverticular disease: a systematic review and meta-analysis of prospective studies

Abstract: PurposeWe conducted a systematic review and meta-analysis of prospective studies of the association between body mass index (BMI) and physical activity and diverticular disease risk.MethodsPubMed and Embase databases were searched up to February 7, 2017. Summary relative risks and 95% confidence intervals (95% CIs) were calculated using a random effects model and nonlinear associations were modeled using fractional polynomial models.ResultsSix cohort studies of BMI and diverticular disease risk (28,915 cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 39 publications
(71 reference statements)
4
47
2
12
Order By: Relevance
“…These findings have important clinical and public health implications because of the growing obesity epidemic worldwide, and add to the wide range of adverse health effects that already have been established to be related to excess weight . The current study suggests excess weight is a risk factor for urinary incontinence and underscores the importance of population‐wide policies and initiatives for prevention of overweight and obesity.…”
Section: Resultsmentioning
confidence: 54%
“…These findings have important clinical and public health implications because of the growing obesity epidemic worldwide, and add to the wide range of adverse health effects that already have been established to be related to excess weight . The current study suggests excess weight is a risk factor for urinary incontinence and underscores the importance of population‐wide policies and initiatives for prevention of overweight and obesity.…”
Section: Resultsmentioning
confidence: 54%
“…Further studies are needed to clarify whether and how fibre intake might interact with the microbiota in reducing diverticular disease risk. Dietary fibre is also associated with less adiposity and lower risk of overweight and obesity [46,47] and could, therefore, reduce the risk of diverticular disease indirectly, since overweight and obesity increase the risk [9]. However, most of the studies included in this analysis adjusted for BMI; thus, it seems that the observed association is largely independent of adiposity.…”
Section: Discussionmentioning
confidence: 92%
“…Collectively, these observations suggest that modifiable risk factors are of major importance for the development of diverticular disease. Overweight and obesity [9], low physical activity [9], smoking [10] and NSAID use [11] are established risk factors for diverticular disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 On the other hand, low physical activity and vitamin D deficiency are known as an emerging risk factor of this disease. 3,4 Vitamin D deficiency is highly prevalent; approximately 25%-57% of the US population 2 and more than 1 billion persons worldwide; 5,6 Also, the benefits of physical activity in the prevention and treatment of CAD have been very well described in adults. 6 Considering the high prevalence of decrease physical activity and vitamin D deficiency in Iran we investigated the prevalence of vitamin D deficiency in angioplasty patients, effect of physical activity and its relationship with coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%